The diffusion of Chukchi “magic words” in Chukotkan and St. Lawrence Island Yupik folklore texts - de Reuse, Willem (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThe languages of the Siberian Yupik region, including Chukotka in the Russian Far East and St. Lawrence Island, Alaska, have been heavily influenced by Chukchi, a genetically unrelated language. In this paper, I focus on Chukchi influences on Yupik folklore. Apparently meaningless “magic words” or formulae used in Yupik tales often appear to be of Chukchi origin. In Chukotka, their Chukchi origin is sometimes recognized by speakers of Yupik, but on St. Lawrence Island, the origin and meaning of the “magic words” is not recognized. The existence of “magic words” provides us with information about the sociolinguistic relationship between Siberian Yupik speakers and Chukchi. The Chukchi were in a position of power with respect to the Siberian Yupiget since they were more numerous, and since the Yupiget depended on them for trade. As a result, the Yupiget saw their Chukchi neighbours and their language as threatening and mysterious, and expressed this feeling by having the foreign protagonists of their tales talk in this strange language.